Adult non-invasive pneumococcal pneumonia in Portugal is dominated by serotype 3 and non-PCV13 serotypes 3-years after near universal PCV13 use in children - Silva-Costa, Catarina; Gomes-Silva, Joana; Santos, Andreia; Ramirez, Mário; Melo-Cristino, José; , The Portuguese Group for the Study of Streptococcal Infections (Frontiers in Public Health, 2023)
Streptococcus pneumoniae in adults. However, the herd effect of vaccinating children in adult NIPP (aNIPP) remains poorly characterized. We determined the serotype distribution and antimicrobial susceptibility of isolates causing aNIPP (>18 years) in 2016-2018 in Portugal; three years with near universal vaccination of children with the 13-valent conjugate vaccine (PCV13), following over a decade of significant PCV use in children in the private market. Among the 1,149 aNIPP isolates, the most frequent serotypes detected were: 3 (n=168, 14.6%), 11A (n=102, 8.9%), 19F (n=70, 6.1%), 23A and 23B (n=62, 5.4% each), 9N (n=60, 5.2%), 8 and 29/35B (n=43, 3.7% each); together accounting for 53% of all isolates. The serotype distribution causing aNIPP was stable in 2016-2018, with the serotypes included in PCV7 still being important causes of disease and serotype 3, a PCV13 serotype, remaining the leading cause of aNIPP. There was an increase in penicillin nonsusceptibility from 17% in 2016 to 24% in 2018 (p=0.018). Some PCV13 serotypes, such as 14, 19A and 19F were associated to resistance, which may have contributed to their persistence. The fact that close to 20% of aNIPP is caused by four non-vaccine serotypes (23A, 23B, 9N and 29/35B) and that there were significant differences in serotype distribution relative to invasive disease, stress the importance of maintaining the surveillance of these infections. The lack of a continued herd effect from vaccinating children and the significant fraction of aNIPP potentially preventable by PCV13 (30%), PCV15 (34%), PCV20 (53%) and the 23-valent polysaccharide vaccine (61%) underscore the importance of considering the broader use of pneumococcal vaccines in adults.